Critical action to redress systemic oppression: a person-centered approach - Vierra, Kristin; Barrita, Aldo; Wong-Padoongpatt, Gloria; Robnett, Rachael D. (Frontiers in Psychology, 2023)
Introduction In 2020, public outcry against police brutality prompted many social media users to post black squares and use the hashtag #BlackLivesMatter (BLM). Many of the people who posted these squares were engaging in performative action in the sense that they failed to engage with BLM’s history and core principles. Drawing from a critical action framework, the current research seeks to more deeply understand what drives people to engage in more versus less impactful forms of action to resist systemic oppression. Methods We employed a mixed-methods and person-centered methodological approach with the goal of providing nuanced information about factors that distinguish among individuals who engage in different forms of action. Participants were 359 undergraduates who reported that they engaged in some form of action to support BLM. Findings Latent profile analysis identified three subgroups (i.e., latent classes) in the larger sample, which we labeled (1) intentional action, (2) intermediate action, and (3) passive action. Participants in each latent class differed from one another in their sociopolitical attitudes, sociodemographic background, and level of action to support BLM. Through the qualitative coding process, the research team unearthed three overarching themes and a range of subthemes that help to explain why the members of each class engaged in different forms of action. Discussion We conclude by proposing a flexible intervention that may motivate individuals to engage in critical action to support BLM.